DOES THE SUFFERING END AFTER CURE FROM COVID? (Journal of Pharmaceutical Negative Results, 2023)
Background: Multisystem involvement of Covid-19 has been known since beginning of the pandemic. Multisystem after-effects or sequelae of covid-19 have been noted and the term 'long Covid' encompasses these signs and symptoms. This leads to prolonged morbidity which have not been adequately addressed by Covid guidelines.The primary aim of our study was to know the spectrum of different sequelae patients have endured after recovery from acute Covid-19 and study their impact on their quality of life.Methods: It was a longitudinal observational study of a cohort of 146 patients who recovered from Covid-19 illness. Patients were enrolled within a week of their onset of Covid symptoms and were followed up monthly for a duration of 6 months with a detailed clinical and investigational pulmonary, cardiac, neurological and psychiatric assessment anda final follow-up after a year. Impact on quality of life was assessed using EQ-5D-3L questionnaire. Those lost to follow up were excluded from the analysis.Results: 120/146 patients qualified for final analysis. Pulmonary sequelae (40%) were the majority among the patients, followed by psychiatric (25%), neurological (21.7%) and opportunistic infections (5.8%). 4/120 died within a year. 62/120 patients documented worsening in quality of life. Sequelae like pulmonary fibrosis, PTSD had the worst impact on the quality of life.95% severe, 54.5% moderate and 25% mild Covid patients reported deterioration in QoL score respectively.Conclusion: Study indicates health related consequences from Covid-19 extend far beyond acute infection andmake significant impact on their quality of life, regardless of the severity of the disease.